Legislasi infisakh akad: Studi konversi akad shirkah dengan akad bai’ di BSI Cabang Bojonegoro - Robbani, Shofa; Ridlwan Hambali, M.; Abdulloh Hafith, Muh.; Hidayat, Wahyu (Asy-Syari’ah : Jurnal Hukum Islam, 2024)
Legislation on contract infisakh in muamalah transactions is an urgent thing to know in order to avoid it. The problem of discrepancies between contracts and practices often occurs in Sharia financial institutions, especially Sharia banks. There are several factors behind the emergence of this case, including the relatively few quality human resources who understand well the implementation of the muamalah contract. Contemporary problems with modern transactions trigger contract incompatibility, such as the conversion of a shirkah contract to a bai' contract which occurred at Bank Syariah Indonesia Bojonegoro Branch. This research aims to explain and describe the legal legislation for annulment (infisakh) of contracts in fiqh muamalah transactions, and the law for converting shirkah (meant Musharakah Mutanaqishah) contracts with bai' (meant Bai’ ‘Inah) contracts at BSI Bojonegoro Branch. This research methodology is field research with a qualitative approach. The research location is Bank Syariah Indonesia Bojonegoro Branch. Data collection techniques were obtained from observation and interviews. Meanwhile, data analysis techniques use data reduction, data presentation, and conclusion. The research results show that eliminating contracts that are not following practice and replacing them with appropriate contracts is an action that must be taken to realize the supremacy of Islamic law in muamalah transactions. Then the conversion of the shirkah contract to bai' carried out by BSI Bojonegoro Branch was the right action, and by the substance of the National Sharia Council Fatwa No. 49/DSN-MUI/II/2005 concerning Contract Conversion and Bank Indonesia Regulation No. 10/18/PBI/2008 concerning Restructuring.